Analysing Research and Development Features: A Comparative Study with Research Management for Sustainable Development in Export Oriented SMEs of Pakistan - Shah, Raza Ullah; Abbas, Kausar (Pakistan Journal of Humanities and Social Sciences, 2025)
This research explores the characteristics of Research and Development (R&D) activities and compares them with research management for sustainable development, focusing on their impact on the export performance of small and medium enterprises (SMEs) in Pakistan. Using a qualitative approach, thirty interviews were conducted with professionals from export-oriented SMEs in Punjab, Pakistan. Discussions focused on the potential of upgrading traditional R&D to align with sustainable development practices. Respondents highlighted the benefits of integrating traditional R&D with research management for sustainable development to enhance export performance. However, the transition requires substantial investment, which poses a challenge for SMEs. Purposive sampling was used, limiting participants to those willing to engage under confidentiality conditions. While qualitative findings offer valuable insights, further quantitative research could provide a broader perspective. The study emphasizes the importance of collaboration between R&D stakeholders and policymakers to harness sustainable research strategies and address systemic barriers. Participants acknowledged that adopting research management for sustainable development could significantly boost exports and help SMEs align with the United Nations Sustainable Development Goals by 2030. The study offers actionable insights for policymakers and stakeholders to strategically leverage research in addressing social and environmental needs, fostering a more sustainable and equitable future. This research identifies best practices and gaps in current R&D approaches, contributing to the literature on sustainable development and offering strategies to enhance SME export performance.